PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR IPS SEJARAH PADA SISWA KELAS VII.3 SMPN 7 DENPASAR - Filfiana Filda; Rulianto (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2020)
The purpose of this study was (1) to find out whether applying the Numbered Heads Together (NHT) type of cooperative learning model could increase the interest in studying Social History History in Grade VII.3 students of SMPN 7 Denpasar and (2) to find out whether the application of the Numbered type cooperative learning model Heads Together (NHT) can improve social studies history learning outcomes for Grade VII.3 students of SMPN 7 Denpasar. The method used in this research is the Numbered Heads Together (NHT) type of cooperative learning method with observation, interview, documentation, and questionnaire data collection. Research shows that student learning outcomes can be seen in Cycle I that the cognitive domain value of students is an average of 6.75 and 52.7% completeness, from the affective domain the value obtained by students is very good 27.7%, good 58.3% and enough 13.3%. While from the psychomotor domain, the scores obtained by students were very good 63.8%, good 27.7% and 8.3% sufficient. In Cycle II the value of the cognitive domain of students is an average of 80 and 100% completeness, from the affective domain the value obtained by students is very good 8.3%, 8.3% good, while from the psychomotor domain the value obtained by students is very good 94 , 4% and good 5.5%